Where's the Fire? Twyla Tharp, Christopher Wheeldon and Alexei Ratmansky in Manhattan - Craine, Debra 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Review of a trio of New York premieres. Twyla Tharp, Christopher Wheeldon and Alexei Ratmansky in Manhattan